Plant Diagnostic Clinic and HLB Lab - Pamela Roberts; Shea Teems; Joubert Fayette; Jamie Burrow (EDIS)
The Plant Pathology program at the UF/IFAS Southwest Research and Education Center is the state and local resource for plant diagnostic services, including HLB (Huanglongbing, or citrus greening) detection, and for insect identification. This brochure covers the center’s history, instructions for sending samples to the HLB lab, answers to frequently asked questions, and center hours and contact information. Written by Pamela Roberts, Shea Teems, Joubert Fayette, and Jamie Burrow, and published by the UF Department of Plant Pathology, July 2015.